A Study on Revisit Intention of The Female Elders: A Case Study of A Beauty Clinic in Bang-Rak District, Bangkok - Chaowpreecha, Pimpaporn; Booranavitayaporn, Suphicha (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2025)
The purpose of this study was to investigate the factors influencing the intention of female elderly customers to revisit a beauty clinic in the Bang Rak area of Bangkok. The target population comprised female elderly individuals aged 60 years and above who used the services of a beauty clinic in Bang Rak, Bangkok, in 2023. A total of 225 participants were included in the study. The research tools included frequency and percentage statistics, standard deviation, One-Way ANOVA, and multiple linear regression analysis. The results of hypothesis testing were as follows: 1. Female elderly customers’ opinions on the service marketing mix at the beauty clinic differed according to their education, average monthly income, and residential area at a statistically significant level of 0.05; 2. The motivation factors influencing female elderly customers’ use of the beauty clinic services varied based on the number of visits, with statistical significance at the 0.05 level; 3. The intention to revisit the clinic also differed based on the number of visits and the decision to use the services, with statistical significance at the 0.05 level; 4. The service marketing mix had a significant influence on the intention to revisit the beauty clinic, at the 0.05 level; and 5. Motivation factors also had a significant influence on the intention to revisit the clinic, with statistical significance at the 0.05 level. The findings contribute to the development of businesses and services for elderly customers.